2003
DOI: 10.1063/1.1631065
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband transmission measurements on waveguides of silicon-rich silicon dioxide

Abstract: We report ultrabroadband measurements on waveguides of photoluminescent silicon-rich silicon dioxide produced by plasma enhanced chemical vapor deposition. Material absorption below 700 nm and waveguide loss above 1300 nm leave a broad spectral region of good transmission properties, which overlaps with the photoluminescence spectrum of the core material. Proposed mechanisms for the material absorption and photoluminescence are discussed based on our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Few loss studies have been recently reported only on slab waveguides with Si-nc. [16][17][18] In this work first we present a thorough study on the physical and optical characteristics of rib-loaded waveguides containing Si-nc obtained by ion implantation of Si into silica to create a well-controlled Si excess profile followed by an annealing step for the precipitation and growth of the Si nanoclusters. The structural and optical characteristics of the active material have been studied, leading to a good knowledge and control of its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Few loss studies have been recently reported only on slab waveguides with Si-nc. [16][17][18] In this work first we present a thorough study on the physical and optical characteristics of rib-loaded waveguides containing Si-nc obtained by ion implantation of Si into silica to create a well-controlled Si excess profile followed by an annealing step for the precipitation and growth of the Si nanoclusters. The structural and optical characteristics of the active material have been studied, leading to a good knowledge and control of its properties.…”
Section: Introductionmentioning
confidence: 99%
“…Boron ions were doped into the device layer by ion implantation to form a p-type layer. The highest implantation energy was 700 keV, and the boron ion concentration was 1 × 10 19 /cm 3 . From simulation calculations, a p-n junction interface was formed at a depth of 1.5-2.5 µm from the surface of the SOI.…”
Section: Design and Fabrication Of A Si Lasermentioning
confidence: 99%
“…Nevertheless, many researchers have been trying to realize Si lasers. For examples, optical gain from Si nanocrystals [2] and light emission from nanocrystaline Si material [3] were reported and Si lasers have been developed using the Raman effect [4] and quantum effects [5]. However, these approaches have disadvantages; from the first to the third requires photoexcitation of electrons, whereas the fourth involves a complex fabrication process, and in addition, these approaches result in low gain.…”
mentioning
confidence: 99%
“…It has attracted much attention owing to its enormous spectral broadening (for instance, it is possible to obtain a white light spectrum covering the entire visible range from 400 to 700 nm), which have many useful applications in telecommunication [42], frequency metrology [43], optical coherence tomography [44], and device characterization [45]. It has to be mentioned, however, that the supercontinuum generation in photonics is, in general, a complex physical phenomenon involving many nonlinear optical effects such as self-phase modulation, cross phase modulation, four wave mixing, and stimulated Raman scattering [46].…”
Section: Generation Of Supercontinuummentioning
confidence: 99%